Imprimés en langues indiennes conservés aux archives historiques oblates, Ottawa - Carrière, Gaston (Anthropologica, 2022)
A previous article on the manuscripts in Indian languages kept in Oblate historical archives in Ottawa seems to have been of interest to scholars and the list of the printed material contained in the same archives have been requested. Even if the catalogue is not very extensive, it is not impossible that books kept in small collections, generally un known, may have works that are not easily found in larger archives or libraries. The present article mentions only the books in Indian languages and is not concerned with the printed material in Eskimo. As can be easily understood, the major part of the items mentioned here is the work of the Missionary Oblates of Mary Immaculate in all parts of Canada. For a more complete idea, one can see Contribution des missionnaires à la sauvegarde de la culture indienne.